Violation Maxim of Principle Cooperation in Indonesian Lawyers Club Presidential Debate Event - Sri Devi,; Rika Ningsih, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This research is motivated by 4 violations maxim principle of cooperation consisting maxim quantity, maxim of quality, maxim of relevance and maxim of implementation/manner that occurred in Indonesian Lawyers Clubs President debate event. The issue in this study is how principle of cooperation was violated in Indonesia Lawyers Club Presidential Debate Event. The purpose of this study is to describe violations maxim of cooperation and it is hoped that in the future, in speaking, values contained in 4 maxims can be applied and it employs a qualitative approach using the content analysis method. The data used in this study are all speeches made by host and resources persons during event, and researcher collected data using note-taking, listening, and documentation techniques. The researcher used content analysis as method of data analysis. The qualitative approach is related to content analysis method because both have aim of understanding content of research and emphasize the theoretical approach to research object, so that approach is relevant to this research because research combines opinions of several experts. the results showed that there were 54 data points on violation principle of cooperation in the Indonesia Lawyers Club Presidential Debate event. The researcher grouped violations into four Grice's maxims of principle of cooperation that had been violated, consisting of 26 data on maxim of quantity, 1 data on maxim of quality, 13 data on maxim of relevance, 14 data on maxim of implementation / manner and there are 2 data that violate in one data where two data have been entered into total number of data analysis. The violations that often occur are violations maxim of quantity, this occurs because participants in speech in the event convey information beyond what interlocutor wants. The violations that often occur are violations maxim of quantity. This occurs because the participants in event convey information that interlocutor does not want, such as when expressing their opinions they often exaggerate. The conclusion of this study, from the 4 maxims have an important role in event of speech, especially in object that the researcher took, but here researcher emphasizes that the application of these 4 maxims, cannot always be applied in cultural values of Indonesian society because they only apply in certain situations and conditions. This is because Indonesian society still upholds the values of friendliness and politeness